Key Success Drivers: Meta-Study Findings Applicable to Large High-Technology Projects - Crosby, Phil (IGI Global, 2012)
Success in project management, and particularly in large, high-technology/IT projects, is not easily achieved. This paper draws together a significant number of case studies and research efforts relating to the success and failure of projects from the last four decades, in what is believed to be the only modern meta-study of its type. The author posits that there is a body of knowledge within the literature from which a number of key indicators or focus areas can be derived for practical application especially in the early stages of projects. Studies encompassing more than 2,800 projects are examined, and the success factors for general, and high technology, projects are newly grouped and ranked as strategic success drivers for use prescriptively by project practitioners and approvers. New correlations between success indicators are presented and the principal drivers examined in further detail to reveal sometimes less obvious characteristics influencing project success. In a series of fieldwork interviews with key staff in high-technology projects, these drivers also emerge consistently as important factors in project success.